Sustainable ferry leasing strategies: the option contract perspective - Cheng, Huibing; He, Hong; Zheng, Shanshui; Zhang, Le; Xu, Lang; Wang, Chunsheng (Frontiers in Marine Science, 2025)
Ferry demand fluctuates unpredictably across different seasons and holidays, posing significant scheduling challenges for operators and resulting in high operating costs and increased carbon emissions. To adapt to market demand variations, ferry operators often supplement their own fleets with leased vessels. Therefore, this paper explores sustainable leasing strategies between ferry leasing companies and operators under uncertain demand conditions, aiming to maximize ferry utilization efficiency. First, this paper develops leasing models under four contract types: wholesale pricing, unilateral options (call and put), and bidirectional options (a classic game-theoretic approach for optimizing decisions under demand fluctuations). Subsequently, it determines the optimal number of leased ferries for each strategy. Then, this paper conducts a comparative analysis of the four contracts, supplemented by sensitivity analysis. Finally, it examines the scenario where an operator purchases ferries instead of leasing them. A case study of a high-speed passenger ferry company in Zhuhai demonstrates that option contracts can mitigate demand uncertainty, thereby improving fleet utilization. The bidirectional option proves more flexible than the unilateral option. However, leasing is not always preferable to purchasing. The findings provide sustainable insights for ferry operators in designing leasing strategies, ultimately reducing operating costs and carbon emissions.